2012
DOI: 10.1155/2012/203734
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Approaches to Investigate the Transport and Activity-Dependent Release of BDNF and Their Application in Neurogenetic Disorders

Abstract: Studies utilizing genetic and pharmacological manipulations in rodent models and neuronal cultures have revealed myriad roles of brain-derived neurotrophic factor (BDNF). Currently, this knowledge of BDNF function is being translated into improvement strategies for several debilitating neurological disorders in which BDNF abnormalities play a prominent role. Common among the BDNF-related disorders are irregular trafficking and release of mature BDNF (mBDNF) and/or its prodomain predecessor, proBDNF. Thus, inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 86 publications
(137 reference statements)
0
28
0
Order By: Relevance
“…In this SNP, val at position 66 is changed to met in the pro region of proBDNF (Lu, 2003b; Hartmann et al, 2012). This SNP does not affect the expression levels or intracellular signaling triggered by the mature BDNF protein.…”
Section: Discussionmentioning
confidence: 99%
“…In this SNP, val at position 66 is changed to met in the pro region of proBDNF (Lu, 2003b; Hartmann et al, 2012). This SNP does not affect the expression levels or intracellular signaling triggered by the mature BDNF protein.…”
Section: Discussionmentioning
confidence: 99%
“…BDNF is a principal neurotrophic factor during brain development as well as in the adult, and has been associated with neuroprotective benefit in a broad range of CNS traumatic and neurodegenerative disorders, including stroke (Zaleska et al, 2009;Nagahara and Tuszynski, 2011;Hartmann et al, 2012). In fact, endogenous BDNF has been implicated in neuronal survival following ischemia (Larsson et al, 1999;Ke et al, 2011), and treatment with exogenous BDNF postischemia has been shown to be neuroprotective and contribute to recovery and neural regeneration (Schäbitz et al, 2007;for review, see Zaleska et al, 2009;Rothman and Mattson, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Although it is desired to quantify directly the absolute amounts of BDNF and proBDNF released (setting aside their cellular contents) to prove their involvement in RISE and LOSS, such quantification is still difficult, since released BDNF is quickly bound to TrkB, p75 NTR and the extracellular matrices 32 and proBDNF is rapidly converted to BDNF 15 . So we chose a strategy to use function-blocking antibodies against endogenous neurotrophin receptors.…”
Section: Discussionmentioning
confidence: 99%